Problematic of Legal Protection Against Women after Ratification the Job Creation Act under the ILO Conventions - Silvia Fadhilah Patriana (RIRAI Publisher, 2022)
It is felt that the overlapping regulations in Indonesia have hampered government programs so far. So that President Jokowi sparked a new regulation, namely the omnibus law with the aim of simplifying regulations in Indonesia so that the omnibus law is believed to be the most relevant solution today. However, this caused a strong reaction by the workers, because it was considered to have the potential to make workers experience marginalization again in the interests of economic development. This research was conducted using a normative juridical approach and intends to explain how legal protection for workers, especially women workers, after the ratification of Law number 11 of 2020 concerning job creation based on International Labour Organization. The results of the research found that no changes were found regarding women's rights in the omnibus law which was also reviewed based on the ILO convention